Effect of Modular Container Design and Load Consolidation Strategy on Cargo Operational Efficiency - Haekal Alfaid Manan, Muhammad (Siber Journal of Transportation and Logistics, 2024)
The modern logistics industry faces significant challenges in improving operational efficiency amid cost pressures, increasing demands for flexibility, and stringent environmental regulations. This study aims to explore the impact of modular container design and cargo consolidation strategies on cargo operational efficiency. Using a literature review approach, the findings reveal that modular container design enhances flexibility and efficiency in space utilization, accelerates loading and unloading processes, and reduces the number of containers required. On the other hand, cargo consolidation strategies integrate multiple shipments into a single delivery to minimize delivery frequency, lower fuel consumption, and reduce carbon emissions. The integration of these two approaches provides a holistic solution for improving logistics efficiency while supporting environmental sustainability. These findings offer strategic insights for logistics industry stakeholders to adopt innovations that boost competitiveness and ensure sustainable operations.